南极长城站附近企鹅栖息地粪土沉积地层放射性核素~(210)Pb定年 - 王自磐; 刘广山; 卢冰; 张卫国; 韩晓菲 (2006)
用γ谱方法测定了南极长城站附近特有生物群落栖息地沉积物中放射性核素含量,地表沉积物中40K,137Cs,210Pb,226Ra,228Ra,228Th.和238U平均比活度,分别为143,7.56,24.1,3.65,5.36,4.15和6.5 Bq/kg.同时测试了阿德雷岛企鹅栖息地粪土沉积地层中放射性核素含量,利用其中的210Pb比活度,210Pbex垂向变化特征,推演沉积物的沉积速率和地质历史年代:其中AD1-a柱样时间跨度约为74 a(1928~2002年),据此计算了沉积速率为0.063 mm/a(r=0.794),并讨论了在南极特定条件下,放射性核素示踪对定年影响以及与区域现代气候环境变化的内在联系. Radioonuclides in the surface sediments in special biological population dropping amended soil collecing from Antarctica have been measured with γ spectrometer.The average contents of ~(40)K,~(137)Cs,~(210Pb,)~(226)Ra,~(228)Ra,~(228)Th and ~(238)U are 143,7.56,24.1,3.65,5.36,4.15 and 6.5 Bq/kg.The specific activity of ~(210)Pb for the core samples in sea birds dropping amended soil,respectively from Ardley Island,have been measured.According to the profiles of ~(210) Pb specific activity,we used CRS model to date the core samples.Which spans about 74 a(1928~2002).Base on the dating,we estimatethe velocity of deposition.Effece of the natural radionuclides treca on dating,relations between storage method of radionuclides and regional climate anomaly variation,and of under the construction of Antarctica have been distributed. 国家自然科学基金资助项目资助(4057600340276037)